Mesopotamian medicine and magic
1 online resource.
Keywords: Mesopotamian Medicine and Magic. Studies in Honour of Markham J. Geller is a thematically focused collection of 34 brand-new essays bringing to light a representative selection of the rich and varied scientific and technical knowledge produced chiefly by the cuneiform cultures. The contributions concentrate mainly on Mesopotamian scholarly descriptions and practices of diagnosing and healing diverse physical ailments and mental distress. The festschrift contains both critical editions of new texts as well as analytical studies dealing with various issues of Mesopotamian medical and magical lore. Currently, this is the largest edited volume devoted to this topic, significantly contributing to the History of Ancient Sciences.